DJ1 represses glycolysis and cell proliferation by transcriptionally upregulating pink1 - Requejo-Aguilar, Raquel (Biochem J, 2015)
DJ1 is a multifunctional protein whose mutations cause autosomal recessive early-onset Parkinson disease (PD). DJ1 loss of function disrupts mitochondrial function, but the signaling pathway whereby it interferes with energy metabolism is unknown. Here, we found that mouse embryonic fibroblasts obtained from DJ1-null (dj1(-/-)) mice showed higher glycolytic rate than those from wild type DJ1 (dj1(+/+)). This effect could be counteracted by the expression of the full-length cDNA encoding the wild type DJ1, but not its DJ1-L166P mutant form associated with PD. Loss of DJ1 increased hypoxiainducible factor-1α (Hif1α) protein abundance and cell proliferation. To understand the molecular mechanism responsible for these effects, we focused on PTEN-induced protein kinase-1 (Pink1), a PD-associated protein whose loss was recently reported to up-regulate glucose metabolism and to sustain cell proliferation (Requejo-Aguilar, Lopez-Fabuel, Fernandez, Martins, Almeida and Bolaños, 2014, Nature Communications 5, 4514). Noticeably, we found that the alterations in glycolysis, HIF1α and proliferation of DJ1-deficient cells were abrogated by the expression of Pink1. Moreover, we found that loss of DJ1 decreased pink1 mRNA and Pink1 protein levels, and that DJ1, by binding with Foxo3a transcription factor, directly interacted with pink1 promoter stimulating its transcriptional activity. These results indicate that DJ1 regulates cell metabolism and proliferation through Pink1.